Conflitos socioambientais urbanos na Apa Bororé - colônia: o caso do parque natural municipal Itaim - Bernardelli Junior, José Maria (2013)
The Metropolitan Region of São Paulo (MRSP) is a complex urban grid composed by 39 municipal districts with a population of 18,3 million people, being the fourth largest human aglomerate worldwide. The city of São Paulo stands as the nucleus of this agglomerate, with a population of 11 million inhabitants. In the Southern part of the city there is a protected landscape named Bororé - Colônia which provides important very important ecosystem services to the region. The creation of this Protected Landscape occurred almost simultaneously to the licensing of the southern section of the Metropolitan Ring Road. As it was anticipated, the ring road construction impacted both the creation of the Protected Landscape limiting its borders and the forthcoming territorial management process. The purpose of this research is to study the interferences of the licensing procedures of the Ring Road in the referred Protected Landscape, analyzing the existing conflicts before its implementation and also the new ones generated right afterwards, especially those related to the settlement of the Itaim Municipal Park within this protected landscape. This research is qualitative in nature addressing a case study, mainly based on literature review, desk research and interviews. It was noticed that the area has been the subject of a number of conflicts over the years, and also that the construction of the road ring contributed significantly to increase them both in number and complexity. The results of the research showed up limitations in the scope of the existing public policies and management procedures which are presently posing difficulties to conflicts resolution in the region. Among a number of recommendations pointed out, it was highlighted the need of a social compensation instrument to be introduced via regulation in a way to meet some basic demands of the population affected by the Ring Road Construction.